Digital Technology: A Catalyst for Financial Inclusion in Developing Countries - Mushtaq, Shazia (Journal of Pakistan Administration, 2022)
Financial inclusion, defined as access and use of formal financial services, is one of the main determinants of sustainable development as it enables the marginalized sections of the society to avail financial services like payments, borrowing, savings and insurance from formal channels. However, most of the people in developing countries use informal channels to fulfill their financial needs, which make them vulnerable to exploitation. In the recent years, digital technology and more specifically digital finance has proved a catalyst for enhancing access and use of financial services in many developing countries. However, some countries like Pakistan have not been able to capitalize this potential despite having digital access like internet connectivity and mobile phone owner ship etc. This study attempts to find out the potential role of digital finance for enhancing financial inclusion in developing countries and what Pakistan can learn from their experiences to mainstream the financially excluded people. Financial inclusion has been recognised as a priority issue for economic development. World Bank and G-20 have led an initiative for increasing financial inclusion in the developing countries, which has been supported by Malinda & Gates Foundation. Resultantly, last decade witnessed an increasing trend in the bank account ownership. The Global Findex database 2017 shows that 69 percent of adults now have an account, as against only 51% in 2011. However, nearly half of the adults still remain unbanked and most of them live in developing countries. There exists a huge gap and untapped market which the traditional banking sector is unable to fill due to higher risks associated with operational costs. However, digital technology like digital finance and mobile banking holds promising prospects for financial inclusion in future but their full potential has not been realized due to barriers which restrict use of financial services in developing countries like financial literacy, unemployment and informal economy. According to a decision tree analysis, both demand and supply size constraints restrict financial inclusion, however, the binding constraint for financial inclusion in Pakistan is informal economy which incentivizes use of cash to avoid taxes and regulation. Accordingly, the lack of demand for digital financial services does not allow full utilization of the available technology and infrastructure. A plausible solution may be increased use of digital finance for Government to People (G2P) and People to Government (P2G) payments, gender inclusion and documentation of economy to increase financial inclusion through mandatory use of formal financial services.